(untitled) (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Adanan IC, Wasli ME, Perumal M, Ying HS. 2020. Characterization of soil properties in relation to Shorea macrophylla growth performance under sandy soils at Sabal Forest Reserve, Sarawak, Malaysia. Biodiversitas 21: 1467-1475. A study was conducted in the Sabal Forest Reserve, Sarawak, to characterize soil properties in terms of soil morphological and physicochemical properties under sandy soil at the reforestation site in comparison with High Conservation Forest soil as well as to assess growth performance of planted S. macrophylla under the sandy soil. Study sites with the size of 25 m x 25 m were established under reforestation sites (Early Establishment of Reforestation Site (ER) and Late Establishment of Reforestation Site (LR)) as well as the High Conservation Forests (HCF-1 and HCF-2). The results from soil morphological properties showed that the soils in ER and HCF-2 plots resemble Saratok series while soils in LR and HCF-1 plot were classified into Buso series. As for soil physicochemical properties, soil in all study sites were strongly acidic in nature with pH (H2O) value less than 5.00 with sandy (more than 55%) at both surface and subsurface soil. The survival percentage of planted S. macrophylla in ER and LR plot was 65 % and 56%, respectively. Long term monitoring on soil properties and growth performance of planted S.marophylla tree are essential in order to continuously provide information on the status of reforestation activity.